2020
DOI: 10.1155/2020/4784701
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Primary Location May Affect Metastasis Pattern for Patients with Stage IV NSCLC: A Population-Based Study

Abstract: Background. Most patients with nonsmall cell lung cancer (NSCLC) were initially diagnosed with distant metastasis. At present, there is no study to clarify the correlation between the primary location of the tumor and the metastasis pattern in advanced NSCLC. So we conducted this study to explored the relationship between the tumor primary location and metastasis pattern in stage IV NSCLC. Methods. A total of 19,295 eligible patients were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…In summary, it can indicate that hospice care is an important factor in good family relationships for patients with advanced NSCLC. 19,25,26 We found it interesting that patients with single bone metastases in NSCLC have longer survival than patients with multiple bone metastases. Because multiple bone metastases in NSCLC usually indicate the high activity and malignancy of these tumor cells, the prognosis is poorer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, it can indicate that hospice care is an important factor in good family relationships for patients with advanced NSCLC. 19,25,26 We found it interesting that patients with single bone metastases in NSCLC have longer survival than patients with multiple bone metastases. Because multiple bone metastases in NSCLC usually indicate the high activity and malignancy of these tumor cells, the prognosis is poorer.…”
Section: Discussionmentioning
confidence: 99%
“…can give patients a “placebo”. 25 This may explain why the survival of BM in married NSCLC patients is better than that in unmarried patients. Moreover, the probability of survival at 3-, 6-, and 12-months for CSS was maintained at about 80%, which is consistent with previous studies that showed that BM of NSCLC patients with positive factors such as medical coverage and family life had higher CSS levels.…”
Section: Discussionmentioning
confidence: 99%
“…Our results supported evidence from previous studies indicating that lung metastasis predicted the best chance of survival while liver metastasis predicted worst outcomes in patients with advanced NSCLC. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…Our results supported evidence from previous studies indicating that lung metastasis predicted the best chance of survival while liver metastasis predicted worst outcomes in patients with advanced NSCLC. 22,23 Previous studies have shown that 19del predicted a better PFS and OS than L858R in patients treated with first-line EGFR-TKIs. 24,25 In the present work, we also found that harboring 19del was associated with favorable PFS in patients treated with icotinib as first-line therapy.…”
mentioning
confidence: 99%
“…Shan et al indicated that the location of the tumor may affect the prognosis of patients with stage IV NSCLC, and primary tumors originating in different lobes had various trends in metastasizing to different organs. Upper lobe tumors more easily metastasized to the brain, middle lobe tumors were more likely to lead to lung metastasis, and lower lobe tumors tended to result in bone metastasis and lung metastasis (15). Ketchedjian and colleagues reported that tumors in the superior segment had a higher potential to induce mediastinal metastasis compared with those from the basal segment (45% vs. 17%, P=0.0003), and there was a significant difference in prognosis between superior segment and basal segment tumors only when tumors were of N2 status (16).…”
Section: Discussionmentioning
confidence: 99%